KAPITALISASI KELUARGA PENDOPO DALAM PEMASARAN POLITIK PARTAI NASDEM PADA PEMILU LEGISLATIF 2019 DI KABUPATEN BLORA - Ishartono, Ilham -; -, Turtiantoro - (Journal of Politic and Government Studies, 2020)
The Nasdem Party is a party that experienced a significant increase in votes in the 2019 Legislative Election. This is inseparable from the Party typology that places voters as consumers as is the practice of campaigning for